1994
DOI: 10.1021/ma00082a014
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Group Dynamics in Glassy Polyisoprene: A Neutron Backscattering Investigation

Abstract: Energy-resolved, elastic neutron backscattering was employed to investigate the methyl group dynamics in polyisoprene between T = 2 K and room temperature. The use of partially deuterated samples (PI-d6, PI-d3, and PI-ds) and of a fully protonated sample (Pl-hg) allowed the separation of the dynamics arising from the methyl group and from the backbone. A two-step relaxation is observed and attributed to the methyl group rotation at low temperatures and to the main-chain relaxation close to the glass transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
148
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(171 citation statements)
references
References 7 publications
20
148
0
3
Order By: Relevance
“…Figure 1 shows the X-ray powder diffraction pattern of the studied sample. The Rietveld refinement indicated that the predominant phase is orthorhombic (P 2 1 2 1 2 1 space group) with unit cell parameters a = 8.09758 (8) findings are consistent with others previously reported in the literature [13,14]. Figure 2 shows the Raman spectra of L-cysteine I at 30 and 300 K. A clear energy threshold at 500 cm −1 (60 meV) could be observed.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Figure 1 shows the X-ray powder diffraction pattern of the studied sample. The Rietveld refinement indicated that the predominant phase is orthorhombic (P 2 1 2 1 2 1 space group) with unit cell parameters a = 8.09758 (8) findings are consistent with others previously reported in the literature [13,14]. Figure 2 shows the Raman spectra of L-cysteine I at 30 and 300 K. A clear energy threshold at 500 cm −1 (60 meV) could be observed.…”
supporting
confidence: 88%
“…The microscopic nature of this transition is still an object of debate. The discussed possibilities include quantum effects near a zero point vibration [7], and methyl group rotation associated with anharmonicity [2,8]. Vibrational modes play a very important role in the conformational arrangement of different functional states and also in the energetic balance of the chemical bonds [9].…”
mentioning
confidence: 99%
“…In the seminal works of Refs. [25] and [26], QENS data for methyl group hopping in polymers were successfully interpreted by introducing a broad distribution of rotational barriers, resulting from the highly disordered nature of the glassy state. In last years, a noticeable amount of experiments in different systems have supported this picture (see Sections V and VI).…”
mentioning
confidence: 99%
“…Dans le même temps, on fait varier un paramètre physique extérieur, en général la température, parfois la pression. L'apparition d'un mouvement dont la dynamique se situe dans la fenêtre expérimentale se manifeste par un élargissement quasiélastique et conduit à une baisse de l'intensité élastique détectée [30,31]. Cette technique permet une inspection rapide de la dynamique de l'échantillon dans un vaste domaine de température.…”
Section: Sauts Sur Deux Sites Non éQuivalentsunclassified
“…On observe également une différence notable entre les deux pentes, ce qui s'explique par l'évolution exacte de la composante quasiélastique avec la température et par la nature plus complexe du terme <u 2 (T) > à haute température. Cette analyse est décite en détails dans les références [30,31] 0. z 'o 820 9'…”
Section: Sauts Sur Deux Sites Non éQuivalentsunclassified